PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA ALFAMIDI CABANG DEPOK - Dea Sapitri; Syawaludin (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the influence of the work environment and workload on employee performance at Alfamidi Depok Branch. The method used is a quantitative method. The sampling technique used saturated samples and obtained 138 respondents. Analysis uses validation tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that the work environment has a positive and significant effect on employee performance, this is shown by the value of tcount > ttable, namely 15.255 > 1.656. Workload has a significant effect on employee performance, this is shown by the t value of 3.488. Thus, tcount > ttable, namely 3.488 > 1.656 and the significance value is 0.001 < 0.05. The work environment has a significant effect on workload and employee performance. The F test results show the calculated F value is 548.832, F table is 3.06, which means that H0 is rejected and H3 is accepted.